Penyusunan E-Modul Menggunakan Kearifan Lokal Bondres Bali untuk Meningkatkan Resiliensi Orang dengan HIV/AIDS - Suarmini, Kadek ayu; Wulandari, Ketut Ayu; Megaputri, Putu Sukma (ARTERI : Jurnal Ilmu Kesehatan, 2025)
Societal stigma often serves as a catalyst for the development of resilience. Resilience, in this context, is defined as an individual's capacity to cope with their personal circumstances. Consequently, enhancing the resilience of People Living with HIV/AIDS (PLWHA) is of significant urgency, as it is directly linked to an improvement in their quality of life. This study aimed to develop an e-module incorporating Balinese local wisdom and to evaluate its effectiveness in increasing knowledge, scores on the Brief Resilience Scale (BRS), social support, and reducing stigma among PLWHA. A quantitative research methodology was employed, commencing with the development of the e-module, which underwent prior expert and content validity testing. Subsequently, an effectiveness test was conducted with 82 PLWHA respondents in Buleleng Regency. The Gregory and Lawshe methods were utilized for the analysis of expert and content validity. Prior to the effectiveness testing, a Kolmogorov-Smirnov test was administered to assess data normality, the results of which indicated a non-normal distribution, thereby necessitating the use of the Wilcoxon test for subsequent analyses. The findings revealed a statistically significant increase in BRS scores, knowledge levels, and family support among PLWHA following the intervention with the "Bondres Bali" e-module. Furthermore, a significant reduction in perceived stigma was observed when comparing pre-intervention and post-intervention states.